Responsabilidade civil por danos ao meio ambiente de trabalho na terceirização de bens e serviços - Cruz, Pollyanna Reis da (2018)
The main objective of the research is to analyze the civil liability of companies for damages to the work environment occurred in their supply chain of goods and services, which was developed by the exploratory research method. For this, we analyze the process of productive restructuring and reorganization of work as a consequence of reflective modernity, based, above all, on Beck's work. As a result of these structural transformations, supply chains are led and articulated by a principal company, which, through contracts for the outsourcing of goods and services, guarantee the development of the economic activity, without its direct link with the workers, which often results in a problem of inadequate allocation of labor responsibility, which falls, in the first instance, on the contracted company, which often does not have economic suitability, which contributes to the precariousness of the work environment and to the not compensation for damages arising from it. To reverse this process of unfair distribution of the risks of the productive activity, so that they fall on the companies that benefit from these activities and are better able to support them and prevent them, it is necessary to reallocate these responsibilities based on values and principles of our legal system, as well as the specific rules on liability. Thus, in the first chapter, these social transformations are studied, as well as the concepts of productive chain, supply chain, outsourcing, goods and services are defined. In the second chapter, we analyze, based on some research, the process of precariousness of the work environment resulting from outsourcing and the importance of recovering the dignity of the human person and the social value of work and of interpreting and guiding the legal system towards them, based on legal principles. In the last chapter, five situations that generate responsibility for damage to the working environment for contracting companies are studied: civil liability arising from the intermediation of labor, civil liability arising from the configuration of economic group, civil liability in service contracts services to third parties, civil liability in contracts for the supply of goods (civil liability of the indirect polluter), residual civil liability for human rights violations. This thesis aims to contribute to the extension of liability for damages to the working environment and its prevention to contracting companies, so that, above all, the responsibility in its general and special preventive function stands out.